Determination of Ethanol In Employee's Blood Who Work In "X" Alcoholic Beverage Industry Using 1-Propanol as an Internal Standard by Gas Chromatography - Harmita, Harmita; Mansur, Umar; Rahmadani, Suchi (Majalah Ilmu Kefarmasian, 2007)
Ethanol not only caused drunk, but also in certain amount it can caused death. Because of the side effect of ethanol was dangerous if there sufficient concentration in blood and the penetration which is relatively easy so it was important to know how much ethanol in blood, especially on official employee in alcoholic beverage industry. A gas chromatography method using a capillary column CBP-10 and flame ionization detector (FID) has been developed and validated for the detection and quatification of ethanol in blood. Gas chromatography was performed in isothermal mode with column temperature 60oC. Helium was used as carrier gas with flow rate 1.0 mL/min. Quantification was performed with the uses of 1-propanol as an internal standard (IS). The method was linear in the concentration range of 0.001-0.8% v/v with coefficient of corelation 0.9998. The lower limit of quantification (LLOQ) was found to be 0.001% v/v. This method was validated with precisions (CV) 0.53-3.47% and accuracies (% diff) 3.86-7.46%. Result of ethanol recovery varied from 96.14-107.46%. The result of validation method fulfilled for the given criteria.